UJI ORGANOLEPTIK JALANGKOTE UBI JALAR UNGU ( Ipomoea batatas L) SEBAGAI UPAYA DIVERSIFIKASI PANGAN - Darni Lamusu (Jurnal Pengolahan Pangan, 2018)
This study aims to determine the organoleptic test of purple sweet potato jalangkote The analysis of research data is designed with Completely Randomized Design which is arranged with 1 factor that is purple sweet potato (J) : J0 = 50% purple sweet potato flour + 50% wheat flour; J1 = 60% purple sweet potato flour + 40% wheat flour; J2 = 70% purple sweet potato flour + 30% wheat flour; J3 = 80% purple sweet potato flour + 20% flour. Based on the results of organoleptic tests showed that the panelist's assessment of jalangkote sweet potato products gave a very real effect on the color, aroma and texture of jalangkote, Then give no real influence on jalangkote sweet potato flavor purple. The best treatment based on panelist appraisal was treatment of J3 ie 80% purple sweet potato flour + 20% flour in color (4.15) and flavor (4.25). Then the best treatment on the scent (4.50) and texture (4.45) is the treatment of 50% purple sweet potato flour + 50% wheat flour